DATING OF TOMBSTONES BY WEAPON IMAGES ON THEM (BASED ON THE STUDY OF STELES OF SULEVKENT CEMETERY) - Musaev, Mahac Abdulaevic; Magomedov, Murad Gazievic (History, Archeology and Ethnography of the Caucasus, 2022)
Experts, who examine Dagestan tombstones, in the absence of a specific date on a tombstone itself or the impossibility of determining it by the content of the inscription or the analysis of texts, use several methods of dating by external elements – by the features of the style (fonts) of texts and by analyzing ornamentation. The subjects of these methods are dated monuments, carefully studied and categorized. Any of these methods is often used separately, the first – by epigraphists, the second – by art historians. Meanwhile, each of them has its drawbacks, and it is clear that the most effective implementation of dating is achieved with their combined application. Another method of dating monuments is to study the objects depicted on them, in particular, weapons. Such studies on Dagestan material have not been carried out yet. As a subject, grave steles of the cemetery of the abandoned settlement of Sulevkent in the Dakhadaevsky district were used, where burials were made at least from the 14th to the middle of the 20th century. Four tombstones depicting sabers and daggers, flintlock pistols and guns, powder flasks and pouches for gazyrs, spears and pikes. The results of the analysis of weapons allowed us to conclude that the monuments belong to the second – third quarters of the 18th century. The dating elements were not only the objects applied to the monuments, but also the absence of certain elements of weapons in the composition of the images. If we exclude images of objects on steles, then all the pieces of monuments under consideration could be dated within a very wide range – from the 16th to the beginning of the 20th century. That is, in certain cases, the analysis of the depicted objects may not serve as an addition to other methods of clarifying or confirming dating, but its only means. The study of weapons as dating elements of tombstones demonstrates that there is a need to study its regional history. In such research, dated tombstones with images of weapons can play an important role. Considering this, it becomes urgent for researchers engaged in identifying monuments to set the task of fixing images of weapon pieces.